Peran Moderasi Work Spirituality pada Hubungan antara Servant Leadership dan Decision to Stay Tenaga Pengajar pada Lembaga Pendidikan di Surabaya - Dominicus Wahyu Pradana (Journal of Management and Business Review, 2022)
Teachers or lecturers are the central figures that have an important role in the assurance of the quality of process education. Maintaining qualified employees (teachers/lecturers) is one of the efforts so they can contribute more optimally. Implementation of the right leadership model is a key factor in this. This research aims to analyze the influence of servant leadership on the decision to stay and analyze the moderating effect of work spirituality on the relationship between servant leadership and the decision to stay. This study is quantitative, using SEM PLS analysis to determine the significant influence of the independent variable on the dependent variable. This study's population was teachers and lecturers at educational institutions affiliated with certain religions in Surabaya. The sample in this study amounted to 103 respondents using purposive sampling and questionnaires distributed online. The study results show that the servant leadership variable significantly influences the decision to stay. So, hypothesis 1 is accepted. While the work spirituality variable does not strengthen or weaken the relationship between servant leadership and the decision to stay. So, hypothesis 2 is not accepted.